In vivo quantitative imaging of hippocampal inflammation in autoimmune neuroinflammatory conditions: a systematic review - Nwaubani, P; Cercignani, M; Colasanti, A (Clinical and experimental immunology, 2022)
The hippocampus is a morphologically complex region of the brain limbic system centrally involved in important cognitive, affective, and behavioural regulatory roles. It has exquisite vulnerability to neuroinflammatory processes, with some of its subregions found to be specific sites of neuroinflammatory pathology in ex-vivo studies. Optimizing neuroimaging correlates of hippocampal neuroinflammation would enable the direct study of functional consequences of hippocampal neuroinflammatory pathology, as well as the definition of therapeutic end-points for treatments targeting neuroinflammation, and their related affective or cognitive sequelae. However, in vivo traditional imaging of the hippocampus and its subregions is fraught with difficulties, due to methodological challenges deriving from its unique anatomical characteristics. The main objective of this review is to provide a current update on the characterization of quantitative neuroimaging correlates of hippocampal neuroinflammation by focusing on three prototypical autoimmune neuro-inflammatory conditions [multiple sclerosis (MS), systemic lupus erythematosus (SLE), and autoimmune encephalitis (AE)]. We focused on studies employing TSPO-targeting positron emission tomography (PET), quantitative magnetic resonance imaging (MRI), and spectroscopy techniques assumed to be sensitive to neuroinflammatory tissue changes. We found 18 eligible studies (14, 2, and 2 studies in MS, AE, and SLE, respectively). Across conditions, the largest effect was seen in TSPO PET and diffusion-weighted MRI studies. No study examined neuroinflammation-related changes at the hippocampal subfield level. Overall, results were largely inconsistent due to heterogeneous imaging methods, small sample sizes, and different population studies. We discuss how these data could inform future study design and conclude by suggesting further methodological directions aimed at improving the precision and sensitivity of neuroimaging techniques to characterize hippocampal neuroinflammatory pathology in the human brain.